Factors associated with the required level of positive airway pressure in patients with obstructive sleep apnea syndrome - Karakurt, Suleyman Emre; Ozcan, Kursat Murat; Ozcan, Muge; Karakus, Mehmet Fatih; Ensari, Serdar; Dere, Haci Huseyin (Annals of Medical Research, 2021)
Aim: To investigate the factors associated with the required level of positive airway pressure as determined by continuous positive airway pressure titration in patients with obstructive sleep apnea syndrome (OSAS). Materials and Methods: A total of 87 OSAS patients were included in the study. The patients were assigned to two groups (low-pressure and high-pressure) based on the positive airway pressure level they required. The groups were compared with respect to baseline clinical characteristics, Muller maneuver findings and polysomnography findings. Results: There were 54 patients in the low-pressure group and 33 patients in the high-pressure group. No significant differences were found between low-pressure and high-pressure groups in terms of mean age, mean body mass index and gender distribution (p>0.05). A statistically significant higher rate of two level obstruction was found in the high-pressure group than in the low-pressure group (p=0.004). Comparison of the groups with respect to polysomnography findings showed mean apnea-hypopnea index (AHI) values of 42.88±26.63 and 54.16±31.29, mean rapid eye movement (REM)-AHI values of 37.38±30.72 and 58.21±26.09 and mean supine-AHI values of 66.04±32.98 and 64.03±31.15 in the low-pressure group versus high-pressure group, respectively. The mean AHI and supine-AHI values were not significantly different between the groups (p>0.05) but the high-pressure group showed a significantly greater mean REM-AHI in comparison to low-pressure group (p=0.002). Conclusion: The number of obstruction levels determined by Muller maneuver and REM-AHI appear to be the prominent factors affecting the positive airway pressure level required in OSAS patients